2016
DOI: 10.1002/lt.24396
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal liver support devices for listed patients

Abstract: An alternative to liver transplantation for patients with liver failure remains an unmet need. In acute liver failure, the ideal extracorporeal liver support device (ELSD) would replace the functions of the failing liver in order to permit spontaneous recovery, given the incredible regenerative potential of the liver, negating the need for transplantation. In acute‐on‐chronic liver failure, an ELSD would ideally support hepatic function until a recovery to liver function before acute decompensation or until li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 69 publications
0
37
0
1
Order By: Relevance
“…Extracorporeal liver devices are considered the next best alternative to liver transplantation by aiding in the recovery of patients to normal health in the case of acute liver failure (ALF) or returning them to a state before decompensation in the case of acute-on-chronic liver failure (ACLF)12. These extracorporeal support systems, aimed at improving the transplant-free survival of patients, may also serve as a bridge to transplantation and/or prevent progress to further severe damage to the liver and other vital organs that could result in end-organ dysfunction13456.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extracorporeal liver devices are considered the next best alternative to liver transplantation by aiding in the recovery of patients to normal health in the case of acute liver failure (ALF) or returning them to a state before decompensation in the case of acute-on-chronic liver failure (ACLF)12. These extracorporeal support systems, aimed at improving the transplant-free survival of patients, may also serve as a bridge to transplantation and/or prevent progress to further severe damage to the liver and other vital organs that could result in end-organ dysfunction13456.…”
mentioning
confidence: 99%
“…These extracorporeal support systems, aimed at improving the transplant-free survival of patients, may also serve as a bridge to transplantation and/or prevent progress to further severe damage to the liver and other vital organs that could result in end-organ dysfunction13456.…”
mentioning
confidence: 99%
“…A meta-analysis has shown that these systems failed to improve survival in ALF [66]. Nevertheless, more well-designed clinical trials in humans are likely needed to fully evaluate these systems efficacy and safety [67].…”
Section: Extracorporeal Liver Support Systemsmentioning
confidence: 99%
“…3 Bacteria-based microswimmers addition, these bacteria-based microswimmers have higher average velocities, and thus, microbeads can be used as drug carriers in drug delivery systems [62]. 4 Artificial microbes: design an efficient microbe to achieve a specific desired output…”
Section: Manipulation Of Motile Microbes: Their Exploitation As Micromentioning
confidence: 99%
“…Although the success rate is very low and technology is limited by several factors, the development of recent fabrication strategies has made it more realistic. Living animal cells are important raw materials for biofabrication of animal-free meat [3], extracorporeal devices [4], and human tissues and organs [5,6]. However, their usage has been overshadowed by limited availability, handling, controlled process development, and limited in vitro survival rate during extended incubation.…”
Section: Introductionmentioning
confidence: 99%